ELECTROSLAG SURFACE OF PRODUCT SURFACES WITH COMPOSITE WEAR-RESISTANT ALLOY - Rybalko, I. M.; Saychuk, O. V.; Zakharov, A. V.; Potoskaev, O. M. (Bulletin of Sumy National Agrarian University. The series: Mechanization and Automation of Production Processes, 2022)
A method of obtaining wear-resistant composite coatings by electroslag surfacing using a current-driven crystallizer and powder wires containing refractory particles of titanium diboride TiB2 has been developed. The thermal conditions of the formation of a thin layer of wear-resistant deposited metal were studied and the kinetics of the transition into it were revealed refractory microparticles from powder-coated wire filler. The bath of liquid slag, having a lower density than that of the molten metal, is constantly above the surface of the metal melt, protecting it from the influence of air. Drops of filler metal, passing through the slag, undergo metallurgical processing and are cleaned of harmful impurities. The direction of slag convection depends on the diameter of the electrode: when welding with a thin electrode, forced electromagnetic convection prevails, the slag sinks near the electrode and rises along the edges of the slag bath, when using a thick electrode, free thermal convection prevails, the slag sinks along the edges of the slag bath and rises near the electrode. The electrodes can be stationary, and their melting will be carried out as a result of the constant rise of the slag and metal baths. If the electrodes are movable, they are continuously fed into the slag bath as they melt. A combination of these methods is possible. The methods of ESN can be classified according to various features, of which technological ones are the main ones. In the process of ESN, two methods of forming the deposited metal are distinguished. One of them involves the free formation of the weld pool melt on a flat horizontal surface, and the second consists in the use of special forming devices – crystallizers made mainly of copper. In them, the molten metal crystallizes in a closed cavity. To prevent overheating, crystallizers are cooled with running water, and their surfaces in contact with slag and metal melts are covered with graphite and other materials, protecting them from electrochemical erosion. In the case of ESN of composite coatings, a granulated hard alloy is poured from above into the slag bath, the melting temperature of which is higher than the melting temperature of the bond metal, the need for which is due to the inadmissibility of secondary melting of some hard alloys, due to which the surfacing of monocoats from such materials is impossible. Hardness and wear resistance are provided by hard alloy particles, and the metal bond holds them on the surface of the part.